ANALISIS PERILAKU MEMILIH MASYARAKAT UNTUK PEMILU 2024 DI TINJAU DARI PERILAKU PEMILIH MASYARAKAT DALAM PILRES 2019 : Studi Kasus Desa Pantai Cermin Kiri Kecamatan Pantai Cermin - Simanullang, Alfon Apriel; Pranata, Dwi Agus; Natalia, Desi; Purba, Endhita Putri; Sihaloho, Fransisco; Harahap, Siti Khoiria; Nasution, Risa Elvina; Sitompul, Yunike Sarah (Universitas Methodist Indonesia, 2023)
Democracy gives people the freedom to choose and determine their course of government and democracy is realized through elections, in an election the community has voting behavior that is heavily influenced by various factors so this study aims to find out what factors influence the people of Pantai vermin kiri village, Serdang berdagai sub-district. Different in determining their choice. This research uses a quantitative method that produces descriptive data regarding information through spoken and written words, the results of the research show that psychological and also rational sociological factors are factors influencing the left mirror beach community in choosing the president and Vice President in 2019 these factors are also factors that will influence society in determining their choices in 2024.